The active compound of the sponge Niphates olemda against Plasmodium falciparum phosphoethanolamine methyltransferase (pfpmt) based on in silico study - F. Frederick; Prawesty Diah Utami; Olivia Mahardani Adam; Fitri Handajani (International Journal of Biomedical Science and Travel Medicine, 2024)
Antimalarial drug resistance to P. falciparum has become a global problem in recent decades. This encourages the need for exploration to find alternative treatments, which come from marine product like Sponge Niphates olemda that contain active substrat. This research was conducted to determine the activity sponge Niphates olemda on P. falciparum phosphoethanolamine methyltransferase (PfPMT) through an in silico study.This research is a pure experimental research using the One Shot Experimental Study research design method. Observations were only made once between the variables studied through three analyzes, namely molecular docking analysis, ADME prediction analysis, and active compound toxicity analysis.The results showed that there were 4 active compounds (Niphateolide A, Kapakahine A, Kapakahine B, and Kapakahine F) that had a better binding affinity than artemisinin so that they had antimalarial potential. However, only Niphateolide A met Lipinski's criteria in ADME analysis, but was more toxic than the other three active compounds and also artemisinin. Based on the results of molecular docking analysis, it was found that the active compound Niphateolide A from the sea sponge Niphates olemda has antimalarial potential on target protein Plasmodium falciparum phosphoethanolamine methyltransferase.